2009
DOI: 10.4317/medoral.14.e654
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic fibro-odontoma: A conservative surgical approach

Abstract: Ameloblastic fibro-odontoma (AFO) is a rare benign mixed odontogenic tumor that occurs predominantly in children and young adults with no gender predilection and anatomic site, usually appearing as a painless swelling. We present a case of an 11-year-old non-Caucasian boy complaining of large painless isolated swelling in the right mandibular body. Intraoral examination revealed a tumoral mass with cortical bone expansion, covered by normal mucosa measuring 4.0 x 2.0 cm, located on both the lingual and buccal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…AFOs are generally asymptomatic slow-growing tumours, although an aggressive behaviour has been reported. Radiographically, AFO appears as a radiolucent, uni-or multilocular, well-delimited area with central radiopacity of variable size and shape, findings compatible with a dental structure that can be associated with an unerupted tooth (Reis et al 2007;Nascimento et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFOs are generally asymptomatic slow-growing tumours, although an aggressive behaviour has been reported. Radiographically, AFO appears as a radiolucent, uni-or multilocular, well-delimited area with central radiopacity of variable size and shape, findings compatible with a dental structure that can be associated with an unerupted tooth (Reis et al 2007;Nascimento et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ameloblastic fibro-odontoma (AFO) is defined by the World Health Organisation (WHO) as an odontogenic tumour composed of proliferating odontogenic epithelium immersed in ectomesenchyme that resembles the interdental papilla. This tumour is, therefore, similar to ameloblastic fibroma, but is associated with inductive changes that lead to the formation of enamel and dentine (Barnes et al 2005;Nascimento et al 2009;Riu et al 2010). AFO is rare, accounting for 3.1 % of all odontogenic tumours (Reis et al 2007;Santos et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of AFO have been reported in the literature (3,6,8,10,11,(13)(14)(15)(16)(17)(18)(19) and it is known to frequently affect individuals below 16 years of age (1,8,20,21). One study has indicated that, when compared with ameloblastic fibroma, AFO more commonly affects individuals belonging to the younger age group; however, this claim can be refuted (19).…”
Section: Discussionmentioning
confidence: 85%
“…Ameloblastic fibro-odontoma (AFO) is an unusual, benign, slow-growing odontogenic tumor occurring mostly during childhood and early adolescence (1)(2)(3)(4). It has a varied radiographic appearance (5,6); multihued calcification is one of the characteristic findings in AFO, wherein, multiple opacities are seen at the center of the tumor (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Radiographically, the AFO presents as a wellcircumscribed unilocular or multilocular radiolucent lesion that may contain a mass in it, with radiopaque foci or variable radiodensity compatible with the material of the dental structure [14][15] . Buchner et al 7 conducted a study in which they revealed that approximately 90% of the lesions were unilocular and that multilocular lesions were uncommon, however, present in 10% of the cases.…”
Section: Case Reportmentioning
confidence: 99%